A case of traumatic diaphragmatic herniation which caused tension hemothorax due to splenic injury resulting from stab wound of the back - Uchida, Yuzo; Tanaka, Koichi; Miura, Takashi; Chujo, Masao; Kawano, Yozo; Arinaga, Mitsuyuki; Shoji, Tsuyoshi (Nihon Kokyuki Geka Gakkai zasshi (Kyoto, 1992), 2000)
We reported a case of traumatic diaphragmatic herniation which caused tension hemothorax due to splenic injury resulting from a stab wound of the back without intraabdominal bleeding. A 20-year-old male was admitted to our hospital for the treatment for left hemothorax resulting from stab wounds of the back. On admission, he was in a pre-shock state because of tension hemothorax, and we performed emergency operation. After left thoracotomy, we found about 3, 000ml blood in his left thoracic cavity. The source of bleeding was the spleen which herniated from a fissure of the diaphragmatic injury resulting from the stab wound by a piece of broken glass. No intraabdominal bleeding was found. We performed splenectomy and sutured the fissure of the diaphragmatic injury. His post-operative course was uneventful.